2017
DOI: 10.1002/hyp.11132
|View full text |Cite
|
Sign up to set email alerts
|

Stream phosphorus dynamics of minimally impacted coastal plain watersheds

Abstract: Understanding natural variation in stream phosphorus (P) concentrations over space and time is critical for understanding natural drivers of catchment behavior and establishing regulatory standards. Across minimally impacted benchmark streams (n = 81) in Florida, spatial variation in mean total P concentrations was large, indicating the importance of geologic controls on catchment solute dynamics. While this variation was significantly predicted by geographic regions, within regions we observed nearly comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 99 publications
(116 reference statements)
2
7
0
Order By: Relevance
“…Riparian fluxes of P from floodplain soils may further enhance this effect when previously immobile floodplain P pools (Noe & Hupp, 2005) mobilize at high flows. Clockwise hysteresis observed in between C and Q during storms in similar coastal plain watersheds (Hensley et al, 2017) reinforces the notion that proximate sources of P mobilized under rising discharge conditions are important to our observed C-Q breakpoint patterns.…”
Section: Breakpointssupporting
confidence: 87%
See 2 more Smart Citations
“…Riparian fluxes of P from floodplain soils may further enhance this effect when previously immobile floodplain P pools (Noe & Hupp, 2005) mobilize at high flows. Clockwise hysteresis observed in between C and Q during storms in similar coastal plain watersheds (Hensley et al, 2017) reinforces the notion that proximate sources of P mobilized under rising discharge conditions are important to our observed C-Q breakpoint patterns.…”
Section: Breakpointssupporting
confidence: 87%
“…We observed strong evidence of lithologic controls on C-Q relationships. As predicted, presence of P-rich Hawthorn Group sediments was significantly correlated with higher FWCs of TP and PO 4 , and also with reduced concentration variation, suggesting that the Hawthorn acts as a relevant, and perhaps dominant, source of phosphorus to regional lakes (Cohen, Lamsal, Korhnak, & Long, 2008) and streams (Hensley et al, 2017). Similarly, Ca FWCs and presence/absence of limestone comported with expectations, with higher concentrations when carbonate exposure increases.…”
Section: Lithologysupporting
confidence: 66%
See 1 more Smart Citation
“…As such, the indication of clockwise TDP hysteresis during larger storms in our study ditch is potentially important because it suggests TDP is rapidly transported to the ditch (Bowes et al., 2009). Faster flow pathways that arrive early in these large storm events are likely enriched in TDP (Hensley et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in our site, DOC concentration of bedrock springs was about 1 mgC/L (Table 1), while some previous studies have shown that groundwater in soil layer could have lower concentrations than 1 mgC/L (Osaka et al, 2010; Sebestyen et al, 2008). In addition, the stream DIP concentration is strongly affected by bedrock geology (Hensley et al, 2017; Wakamatsu et al, 2006). Therefore, the influence of bedrock groundwater discharge on the spatial distribution of stream DOC, DIN and DIP concentrations could vary greatly depending on the catchment characteristics, for example, bedrock geology and chemical properties of soil.…”
Section: Discussionmentioning
confidence: 99%